The Effect of Tofu Liquid Waste Treatment Using EM4 Biofilter to Reduce TSS (Total Suspended Solid) and COD (Chemical Oxygen Demand) Levels - Bakkara, Putri Stephanie; Harahap, Sampe; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Â AbstractTofu liquid waste is rich in TSS and COD so it needs to be treated before being discharged into the environment. This study aims to reduce TSS and COD in tofu wastewater using biofilter added to EM4, which was conducted in May-July 2019. The design of this experiment uses 3 kontrols, 3 treatments and 3 replications with consisting of the addition of 17 ml, 20 ml and 23 ml EM4. The treatments were all placed in anaerobic and aerobic drums. Then tofu liquid waste that is biofilter using EM4 is tested to determine the TSS and COD concentrations. The processed waste is then used to raise Carp (CyprinusCarpio) as a test fish. The results of this study indicate that after tofu wastewater is processed using biofilter added EM4, it turns out that the concentration of TSS in water is reduced at P2 (20 ml) which is 150 mg / L and decreases by 97.61%, and the COD concentration is reduced at P2 (20 ml ) ie 106.33 mg / L and a decrease of 98.89%. Goldfish (CyprinusCarpio) in the use of tofu liquid waste that has been processed to get percentage of a livelihood of 93.33% in P2U1. It can be concluded that granting EM4 in Biofilters is able to reduce TSS and COD in the liquid waste industry know and already meet the requirements of raw water wastewater according to regulation Minister of Environment No 5 year 2014.Keyword : Tofu Liquid Waste Effective microorganism 4, Cyprinus Carpio